Model Inovasi Kebijakan Daerah untuk Integrasi Ketahanan Perkotaan dalam Perspektif Pertahanan: Studi Komparatif Kota-Kota Global - Yunianto Rahadi Utomo; Irdam Ahmad; Lukman Yudho Prakoso; Bambang Irwanto (Research and Development Agency Ministry of Home Affairs, 2026)
Urban areas increasingly function as strategic nodes in national resilience systems in responding to multidimensional threats such as terrorism, climate change, cyber disruption, and hybrid conflict. However, in the Indonesian context, the integration of resilience and defense principles has not been systematically incorporated into local development policies. This study aims to formulate a local policy innovation model for integrating urban resilience into regional planning and governance systems. This research employs a qualitative approach with a comparative case study design, examining eight global cities—Singapore, New York, London, Tel Aviv, Dubai, Tokyo, Seoul, and Copenhagen—based on literature and policy document analysis. The analysis focuses on comparing spatial, technological, and social dimensions of urban resilience. The findings identify three main integration patterns: (1) spatial resilience through risk-based spatial planning and resilient infrastructure, (2) digital resilience through technology-based monitoring and response systems, and (3) social resilience through community preparedness and participation. The variation across cities is influenced by threat characteristics, institutional capacity, and technological maturity. The novelty of this study lies in the formulation of an operational and adaptive three-pillar policy innovation model that can be integrated into local planning instruments such as RTRW and RPJMD. This model provides practical guidance for local governments in developing risk-based urban resilience systems.